2010
DOI: 10.1183/09031936.00160609
|View full text |Cite
|
Sign up to set email alerts
|

Assaying for circulating osteopontin in practice: a technical note: Fig. 1—

Abstract: These data suggest that the extra sensitivity provided by AF bronchoscopy improves the ability of trainees to make the correct diagnosis at bronchoscopy and suggest a role for AFI in teaching hospitals in training inexperienced bronchoscopists.Our preliminary study shows how a ''slide bank'' of bronchoscopic images can be used to asses the diagnostic performance of a bronchoscopic system by multiple operators. We believe it is valid and eminently transferable to other studies. This work needs to be repeated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The reason of serum mean OPN differences between human studies were not clear. The results of circulating OPN levels may be variable depending on the type of sample (plasma vs serum), ages, races, detection method, and choice of ELISA kit (12, 15). …”
Section: Discussionmentioning
confidence: 99%
“…The reason of serum mean OPN differences between human studies were not clear. The results of circulating OPN levels may be variable depending on the type of sample (plasma vs serum), ages, races, detection method, and choice of ELISA kit (12, 15). …”
Section: Discussionmentioning
confidence: 99%
“…The levels of OPN in various cancers including ovarian, head and neck, breast, liver and cervical cancer are highly dependent on the ELISA kit utilized to measure its concentration. Significant differences in assay results with little correlation between those of the 2 commercial kits have been observed 52 . The lack of a strong correlation between the 2 methods indicates a systematic bias proportional to the measured value (proportional error).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of a strong correlation between the 2 methods indicates a systematic bias proportional to the measured value (proportional error). The proportional error is due to the nonlinearity of the 2 measures and the amplification generated by different enzymes in the ELISA assay 52 . Since both assays measure the same target molecule, it is difficult to precisely determine which method is biased and in which direction 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Two different ELISA kits (IBL and R&D Systems) were used to determine FL-OPN levels because it has previously been demonstrated that these ELISA systems can have discordant results [35, 39, 40]. Analysis with the IBL kit showed that the levels of OPN were markedly elevated in both patients with DF (median, 25,951 pmol/L; 9.2-fold increase) and patients with DHF (median, 27,550 pmol/L; 9.7-fold increase), as compared with the HCs (2,814 pmol/L; Figure 1A).…”
Section: Resultsmentioning
confidence: 99%